2022
DOI: 10.1177/03913988211070309
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the effect of the aspect ratio of cylindrical surface microstructure on von Willebrand factor damage

Abstract: Hemorrhagic episodes in patients carrying mechanical circulatory support represent a severe clinical complication. These bleeding episodes may originate from a reduced functionality of von Willebrand factor (VWF), a multimer protein pertinent to form a hemostatic plug. The reduced functionality is due to increased loss of high molecular weight von Willebrand factor multimers (HMWM-VWF), a phenomenon that is facilitated by device-induced increases in shear stress to which VWF is exposed. However, in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The surface microstructure of the material, such as roughness and hydrophilicity, may cause a different level of damage to the blood. 5,24 Therefore, the influence of material surface microstructure on blood damage should also be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface microstructure of the material, such as roughness and hydrophilicity, may cause a different level of damage to the blood. 5,24 Therefore, the influence of material surface microstructure on blood damage should also be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, it is often accompanied by the occurrence of hemocompatibility complications in clinical treatment, mainly including hemolysis, thrombosis, and gastrointestinal bleeding. 5,6 Hemolysis has been confirmed to be caused by the damage of red blood cells, thrombosis is mainly caused by platelet activation due to high shear stress, and the main trigger of gastrointestinal bleeding complication is the degradation of high molecular weight von Willebrand Factor (VWF). In addition to shear stress and exposure time, 7,8 which are considered to be two key mechanical factors contributing to blood damage, the blood-contacting materials in Mechanical Circulatory Support Devices (MCSDs) are equally likely to cause blood damage.…”
Section: Introductionmentioning
confidence: 99%
“…The details of collecting samples for VWF test were described in our previous research. 15 The perfusion tests were performed four groups under same condition using the same batch of plasma. The same procedure was repeated for each experiment.…”
Section: Experimental Circuit For In Vitro Test and Experimental Spec...mentioning
confidence: 99%
“…In addition, we also found that VWF damage can be significantly reduced when the aspect ratio of material surface micro-structure (regular millimeter surface micro-structure) exceeds a certain range. 15 These studies indicated that the changes of interface factors caused by surface modification can also affect VWF damage besides mechanical factors. The development of micro-machining technology makes it possible to construct bionic micro-structures (regular surface micron-scale structures) on the material surface.…”
Section: Introductionmentioning
confidence: 96%